Peran Kepercayaan Dalam Memediasi Service Quality dan Price Terhadap Keputusan Pembelian Konsumen - Noviana, Nining; Rachma, N.; Sholehuddin, Sulton (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This study aims to instill the role of consumer trust as a mediating variable in the relationship between service quality and price on purchasing decisions at TW Café & Eatery Malang. In facing increasingly tight competition in the coffee shop business, business actors need to improve shared services, set competitive prices, and build customer trust. This study uses a quantitative approach with a purposive sampling technique on 95 customers, and is analyzed using the Partial Least Squares (PLS) method through SmartPLS 4 software. The results of the analysis show that service quality has a significant effect on purchasing decisions through consumer trust, while price does not provide a significant effect through the trust variable. Therefore, it can be concluded that consumer trust is an effective mediator in the relationship between service quality and purchasing decisions, but has no effect in relation to price. Keywords: Trust, Service Quality, Price, Purchase Decision